COVID-19 vaccine hesitancy : mobile education initiatives to improve vaccination uptake among healthcare workers - Nailul Muna AM; Karniza Khalid; Siti Noriani AW; Irma Liyana M; Siti Zulaiha CH; Mohamad Zamri K; Othman W (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Vaccine hesitancy is a global threat to public health contributed by misinformation and lay beliefs about diseases and health. Our study aimed to assess preparedness and intent to receive COVID-19 vaccine among healthcare workers in a single institution in northwest Malaysia and assess the feasibility and efficacy of our mobile education programme to overcome vaccine hesitancy among healthcare workers. Our initial survey among 1,616 respondents found that 25.3% of healthcare workers either refused or were hesitant towards COVID-19 vaccination; 238 respondents (58.2%) of which with no absolute clinical contraindication. Our multifaceted mobile education programme involved: (i) series of continuous medical education (CMEs) to 72 elected liaison officers, (ii) small scale briefing session to individual unit and/or department upon request, and (iii) a one-to-one counselling session upon request. The programme took the course of over four weeks prior to the actual vaccination drive. Re-assessment of intent to receive COVID-19 vaccine found a significant reduction of healthcare workers refusing COVID-19 vaccination without absolute contraindication (25.3% vs. 2.8%). The most common reasons cited among those who were still hesitant were due to pregnancy (non-first trimester) and planning to conceive in the near future. Our study demonstrated the efficacy of physical interaction and teaching session to allow rapid communication and gives better understanding, particularly when dealing with myths, misinformation and misconception related to COVID-19 vaccine.